Sustainable and Safe Public Spaces for Everyday Life in Socio-Spatially Segregated Communities - Karol Margarita López Valenzuela; Dulce Esmeralda García Ruíz; Verónica Livier Díaz Nuñez (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
How es Item possible to achieve a conceptual relationship between sustainability , security and public space in sociospatially segregated areas? The article aims to address the main theoretical positions on the topic of sustainability linked to environmental safety in public spaces in such a way that Item seeks to glimpse and mitigate que these new spaces conditions are that influence the safety of neighborhoods and cities on a metropolitan scale . Starting from a critical /reflective stance and through documentary analysis , the aim es to establish a semantic network , as well as a cloud of words to determine the level of concurrence in this way to establish que relationship exists or does not exists between sustainability , security and public space in socially segregated areas , especially , this article is a documentary and exploratory document that allows us to clarify the problems present at metropolitan scales in Latin America .